Pendugaan NiLai Erosivitas Hujan Menurut Metode Analysis Data Alat Penakar Hujan Otomatik, Metode BOLS Dan RRL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT A comparative study on rainfall erosivity from the forest plantation was conducted to evaluate the best method of prediction. An accurate value of rainfall erosivity is important to assess soil erosion and run off rates prediction of a given land area using USLE equation. There were three methods of erosivity prediction, namely prediction using automatic rain gauge, bols and RRL methods. Each procedure has some characteristics which conforms specific rainfall data to produce the erosion. The result showed that if the rainfall data distribution collected using an automatic rain gauge were limited, one could use data collected using an ordinary rain gauge (Ombro-meter type) and then analyzed them using Bols's (1978) or RRL's (1984) equations. Whenever the data of rainfall were rather heavy (32 - 140 mm/ month) and distributed almost evenly during the whole month (13 - 20 rain days) the RRL's equation could be used properly. On the other hand, whenever the data of rainfall were low, the Bols's equation was more approppriate for erosivity prediction. For heavy rainfall (150 - 300 mm/month) the use of RRL's equation gave rather over estimate results. It is suggested to environmental practitioners to install at least the manual type of rain gauge if the automatic ones are expensive. Data from those rain gauges can be used to analyze the two methods of rainfall erosivity prediction.